PENERAPAN METODE CARD SORT DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS VIII SMP NEGERI 2 PALAKKA - Sarea, Muh Syahrul; Akbar, Muh; Darniati, Darniati (IAIN Bone, 2023)
The purpose of this research is to enhance the students' learning motivation by using the card sort method. The type of research employed is Classroom Action Research. The study takes place at SMP Negeri 2 Palakka on Jln. Poros Pasempe, specifically in the village of Ureng. The research subjects consist of 20 students from Grade VIII at SMP Negeri 2 Palakka, comprising 14 female students and 6 male students. This study adopts a qualitative approach. The data collection techniques utilized in this research include observation, interviews, documentation, and direct involvement during the teaching and learning process between teachers and students. The data are analyzed using descriptive statistical analysis. The research is conducted in two cycles. Cycle I involves the implementation of the card sort method for teaching the material, followed by Cycle II, which incorporates the card sort method along with practice and a question-and-answer session. The results of this study indicate that the application of the card sort learning method effectively improves the learning motivation of Grade VIII students in SMP towards the subject of Islamic Education (PAI) with the specific topic being the various types of prostration (sujud syahwi, sujud tilawah, and sujud syukur). This is evident from the observation data on learning motivation, where the indicators of diligence in learning show an increase from 75% to 95%, interest in learning with the indicator of active participation in the learning process increased from 25% to 70%, enthusiasm in learning increased from 45% to 90%, and self-reliance in learning with the indicator of self-confidence increased from 25% to 65%.Keywords: Learning Motivation, Card Sort, Islamic Education Subject